Multiculturalism or Cultural Amnesia? Why America and Britain Must Preserve Their Identity for the Coming Experience Economy - Nwoke, Uzoma Ugochukwu Nwoke; Adediran, Adewale Gbolagade Adediran; Ogbeide-Ihama, Mojisola Amenze Ogbeide-Ihama (African Journal of Stability and Development (AJSD), 2025)
This commentary examines the evolving nature of culture in the 21st century, positioning culture as a dynamic force driving soft power and the experience economy. It raises critical questions: Should liberal democracies, such as the United States and the United Kingdom, uphold their historical cultural identities amidst increasing multiculturalism? Or does this lead to the erosion of their foundational values? The paper argues that both nations possess distinct, valuable identities rooted in their historical and political systems. While acknowledging multiculturalism’s role in promoting diversity, the commentary cautions against cultural dilution when the host nation’s values cease to be prioritised. The commentary proposes a managed pluralism approach, drawing lessons from nations that balance international engagement with preserving core identity, suggesting this is crucial for these democracies to maintain influence in a world that increasingly values cultural experiences over the purchase of goods and services.